2009
DOI: 10.2319/042308-225.1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for the Assessment of Three-Dimensional Tooth Movement during Orthodontic Treatment

Abstract: Objective: To (1) evaluate the stability of palatal rugae as landmarks for superimposition of dental casts and (2) establish a three-dimensional superimposition method of maxillary dental casts for analyzing orthodontic tooth movement. Materials and Methods: The sample consisted of dental casts obtained from 10 patients treated with extraction of bilateral maxillary first premolars and placement of three palatal miniscrews as anchorage for retraction of the anterior teeth. Dental casts were measured by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 11 publications
1
54
0
Order By: Relevance
“…Many authors have investigated the use of the palatal rugae as reference points for measuring tooth movements on serial dental casts [3][4][5][6][7] and on 3D digital models. 21,23,24 In a study of changes occurring in 15 patients who underwent extraction of four premolars, Peavy and Kendrick 6 reported that the lateral ends of the rugae close to the teeth followed the teeth in the sagittal plane, while the so-called O point on the midsagittal plane was least affected. Van der Linden 7 evaluated changes in rugae and interrugal dimensions in 65 normally growing children (aged 6 to 16 years) and in six orthodontically treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many authors have investigated the use of the palatal rugae as reference points for measuring tooth movements on serial dental casts [3][4][5][6][7] and on 3D digital models. 21,23,24 In a study of changes occurring in 15 patients who underwent extraction of four premolars, Peavy and Kendrick 6 reported that the lateral ends of the rugae close to the teeth followed the teeth in the sagittal plane, while the so-called O point on the midsagittal plane was least affected. Van der Linden 7 evaluated changes in rugae and interrugal dimensions in 65 normally growing children (aged 6 to 16 years) and in six orthodontically treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…The orthodontic miniscrew may serve as an alternative reference landmark, but only in a limited number of cases. 22,23,25 Jang et al 23 evaluated the stability of palatal rugae using digital models superimposed on three miniscrews as registration landmarks and concluded that the medial points of the third palatal rugae and the shape of the palatal vault were stable throughout orthodontic treatment with premolar extraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The superimposing method has been previously described. 21 The superimpositions were performed within the same rat's material.…”
Section: D Superimpositionmentioning
confidence: 99%